2005
DOI: 10.1007/s10156-005-0385-z
|View full text |Cite
|
Sign up to set email alerts
|

HBV reactivation with fatal fulminating hepatitis during rituximab treatment in a subject negative for HBsAg and positive for HBsAb and HBcAb

Abstract: A 51-year-old man who was hepatitis B surface antigen (HBsAg)-negative and positive for anti-hepatitis B surface antigen (anti-HBs) and anti-hepatitis B core antigen (anti-HBc), during rituximab therapy for chronic Lymphocytic leukemia, developed reactivation of hepatitis B virus (HBV) infection with hepatitis that proceeded towards hepatic failure and death in spite of lamivudine therapy. HBsAg remained persistently negative, notwithstanding a high HBV-DNA titer. Our observation, following other cases of fata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
0
4

Year Published

2007
2007
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(70 citation statements)
references
References 12 publications
2
64
0
4
Order By: Relevance
“…This recommendation is supported by isolated case reports of reactivation. 9,15,16,26 Because of the variations in HBV profile among different populations, the recommendations made by the British Columbia Cancer Agency may not be entirely applicable to HBV endemic regions (eg, Asia); 1 in 3 patients with newly diagnosed lymphoma will require prophylactic lamivudine if these recommendations are followed as suggested by our data. On the basis of the low risk of HBV reactivation (1.5%) reported in the current study, the routine use of antiviral prophylaxis in this group of patients might not be substantiated.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This recommendation is supported by isolated case reports of reactivation. 9,15,16,26 Because of the variations in HBV profile among different populations, the recommendations made by the British Columbia Cancer Agency may not be entirely applicable to HBV endemic regions (eg, Asia); 1 in 3 patients with newly diagnosed lymphoma will require prophylactic lamivudine if these recommendations are followed as suggested by our data. On the basis of the low risk of HBV reactivation (1.5%) reported in the current study, the routine use of antiviral prophylaxis in this group of patients might not be substantiated.…”
Section: Discussionmentioning
confidence: 93%
“…13,14 Of concern, there have also been reported cases of HBV reactivation in patients with past HBV infection (HBsAg negative, HBcAb positive) during the course of chemotherapy and/or immunotherapy, sometimes proving fatal. 15,16 Nevertheless, it remains uncertain whether patients with past HBV infection are at a substantial risk for reactivation of latent HBV. 17 Hence, in the current study, we sought 1) to elucidate the incidence of past HBV infection among a population of lymphoma patients and 2) to examine its effect on the risk of HBV-related complications after systemic treatment.…”
mentioning
confidence: 99%
“…But it is of note that accumulating evidence shows that patients with past HBV infection are still at risk for reactivation after use of anticancer agents, especially given rituximab, and may be considered for prophylaxis [12,13,25]. Although this issue was not explicitly expounded in our manuscript due to the small case number, it may be considerate as an important issue in future studies.…”
Section: Discussionmentioning
confidence: 92%
“…However, a study by Sera et al [9] has shown that rituximab can affect the immunity against HBV, consequently increasing viral replication. In fact, there were several case reports of fulminant liver failure due to HBV reactivation in patients with either chronic HBV infection or past HBV infection (HBsAg negative, HBcAb positive) after treatment with rituximab, sometimes proving fatal [10][11][12][13]. The events leading to HBV reactivation during rituximab given alone or in combination with chemotherapy are presently being paid close attention.…”
Section: Introductionmentioning
confidence: 99%
“…Z reguły R-HBV rozwija się po 3 cyklach chemioterapii, niekiedy jednak może rozwinąć się już po pierwszym cyklu jak również tuż po zakończeniu terapii [11], a niekiedy nawet aż po 170 dniach od zakończenia tego onkologicznego leczenia [16]. W wyniku R-HBV może dochodzić do niewydolności wątroby: od bezżółtaczkowego zapalenia wątroby do śmiertelnej niewydolności wątroby, występującej od 5% do 40% pacjentów leczonych chemioterapią [16,17].…”
Section: R-hbv U Pacjentów Hbsag Dodatnichunclassified